Analisis Laju Pencucian Tanah Salin dengan Menggunakan Drainase Bawah Permukaan - Nibras Nasyirah; Dedi Kusnadi Kalsim; Satyanto Krido Saptomo (PERTETA, 2015)
Leaching process with subsurface drainage is needed to solve the salinity problem. This research was conducted to determine the leaching rate of saline soil by contaminants flow in the soil experiments, and determine the accuracy of ILRI’s formula (1994) that used in the calculation. Data was collected in some experiments, the experimental of soil physical properties, salt contamination, and soil leaching. The experiments showed the different leaching time to reduce concentration to the desired level, 0.07, 0.13, and 0.08 days, respectively for the percolation rate 1035.73, 1614.12, and 1888.52 mm/day. It is influenced by concentration of dissolved salts (Ct), rate of percolation (q), water storage in field capacity (Wfc), and permeability (K). However there is has a differentation between an experiment and calculating result, so for this condition needs a development of formula that issued by ILRI (1994) with adding a correction coefficient for Wfc value, 0.076, 0.078, and 0.042 for experiments 1, 2, and 3, so the calculation results may approach by the real condition.